The Knowledge, Attitudes, and Practices of Academic Librarians Toward Open Educational Resources: Developing and Validating the OpenEd-LibKAP Scale - Richards, Riley; Monnin, Jennifer; Whitman, Kristin (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2026)
Objective – The aims of the open education (OE) movement can be supported by academic librarians, although most librarians have not had formal training on open educational resources (OER). The objective of this study is to design and validate a survey instrument to measure the knowledge, attitudes, and practices (KAP) of academic librarians toward OER to be used in future research projects.Methods – The Open Education - Librarian Knowledge, Attitudes, and Practices (OpenEd-LibKAP) scale was developed by experienced academic librarians and assessed for content validity by OER subject experts. A pilot study was conducted to assess internal consistency, and a second round of the survey was administered to an international group of current academic librarians. Exploratory factor analysis (EFA) was performed on the results.Results – The final instrument includes 50 questions, with 22 items in the knowledge domain, 16 items in the attitude domain, and 12 items in the practices domain. The KAP factors positively correlate in an expected manner, with a range from .404 to .591. The individual domains have high markers of reliability, implying a degree of confidence in our findings and future uses of the tool.Conclusion – The OpenEd-LibKAP Scale developed through this study can be used by library administrators, OER program administrators, librarian researchers, and OER researchers to more accurately measure and assess academic librarian OER competencies, beliefs, and behaviours related to OER.